Characterization of DNA Methylation and Screening of Epigenetic Markers in Polycystic Ovary Syndrome - Cao, Pengbo; Yang, Wanting; Wang, Peijun; Li, Xihe; Nashun, Buhe (Frontiers in Cell and Developmental Biology, 2021)
Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine and metabolic disorder in women which is characterized by androgen excess, ovulation dysfunction and polycystic ovary. Although the etiology of polycystic ovary syndrome is largely unknown, many studies suggest that aberrant DNA methylation is an important contributing factor for its pathological changes. In this study, we investigated DNA methylation characteristics and their impact on gene expression in granulosa cells obtained from PCOS patients. Transcriptome analysis found that differential expressed genes were mainly enriched in pathways of insulin resistance, fat cell differentiation, and steroid metabolism in PCOS. Overall DNA methylation level in granulosa cells was reduced in PCOS and the first introns were found to be the major genomic regions that were hypo-methylated in PCOS. Integrated analysis of transcriptome, DNA methylayion and miRNAs in ovarian granulosa cells revealed a DNA methylation and miRNAs co-regulated network and identified key candidate genes for pathogenesis of PCOS, including BMP4, ETS1 and IRS1. Our study shed more light on epigenetic mechanism of PCOS and provided valuable reference for its diagnosis and treatment.